Synapse‐selective rapid potentiation of hippocampal synaptic transmission by 7, 8‐dihydroxyflavone. Issue 4 (3rd October 2018) - Kobayashi, Katsunori; Suzuki, Hidenori
Abstract: Aim: The identification of 7, 8‐dihydroxyflavone (DHF) as a small molecule agonist for tropomyosin‐related kinase B (TrkB) facilitated understanding of the role of TrkB signaling in regulating higher brain functions. DHF can penetrate the blood‐brain barrier after systemic administration and changes the performance of cognitive and emotional behavioral tasks. However, it is poorly understood how DHF modulates neuronal functions at cellular levels. Aiming to understand the cellular basis underlying DHF‐induced modifications of the brain functions, we examined the effects of DHF on the hippocampal excitatory synaptic transmission. Methods: Field excitatory postsynaptic potentials were recorded using hippocampal slices prepared from adult male mice. Effects of bath‐applied DHF on the synaptic efficacy were examined. Results: We found that DHF induced robust synaptic potentiation at the mossy fiber to CA3 synapse. DHF had minimal effects at other hippocampal excitatory synapses or at immature mossy fiber synapse in juvenile mice. The TrkB receptor blockers K252a and ANA‐12 did not affect the DHF‐induced synaptic potentiation. Drug screening revealed that relatively low concentrations of 2‐aminoethoxydiphenylborane blocked the DHF‐induced synaptic potentiation. Conclusion: Our results demonstrate that DHF selectively potentiates hippocampal mossy fiber synaptic transmission via a TrkB receptor‐independent mechanism. This novel neuromodulatory effect of DHF may influence higher brain functions by itself or together with the activation of the TrkB receptor. The rapid induction of the potentiation implies its potential importance in the acute behavioral effects of DHF. Abstract : We show that acute 7, 8‐dihydroxyflavone (DHF) administration selectively potentiates hippocampal mossy fiber to CA3 synaptic transmission. This DHF‐induced synaptic potentiation was found to be independent of TrkB receptor activation.